Care or collusion in asylum seeker detention - Briskman, Linda; Zion, D.; Loff, B. (Routledge Tailor Francis, 2012)
This paper explores ethical questions arising from the work of health practitioners in immigration detention centres in Australia. It raises questions about the roles of professional disciplines and the ways in which they confront dual loyalty issues. The exploration is guided by interviews conducted with health professionals who have worked in asylum seeker detention and an examination of the outsider advocacy role undertaken by the social work profession. The paper discusses the stance taken by individuals and professional associations on participation in controlled settings, including as participant, bystander and advocate, and asks when the provision of care becomes collusion with oppression.